Pengembangan Bahan Belajar Berbasis Metode Bermain Untuk Guru dalam Pembelajaran Orientasi dan Mobilitas Pemahaman Konsep Arah bagi Peserta Didik Hambatan Penglihatan - Suherman, Suherman; Rochmat Wahab (Lembaga Teewan Journal Solutions, 2026)
This study aimed to develop game-based learning materials for Orientation and Mobility instruction on directional concept comprehension for students with visual impairments and to examine the validity, practicality, and effectiveness of the developed product. This study employed the Research and Development (R&D) method using the ADDIE development model, which consists of the Analyze, Design, Develop, Implement, and Evaluate stages. Data were collected through observations, interviews, questionnaires, and tests and were analyzed using descriptive quantitative and qualitative techniques. The results showed that the developed learning materials met the validity criteria based on evaluations conducted by material experts, media experts, and instrument experts. The field trial indicated that students' responses achieved a score of 95, categorized as Very Good, while teachers' responses obtained a score of 91.30, categorized as Good. The effectiveness test also demonstrated an improvement in students' understanding of directional concepts after using the developed learning materials. Therefore, the game-based learning materials were considered valid, practical, and effective, making them suitable as an alternative learning resource for Orientation and Mobility instruction for students with visual impairments.